Perceived effects of drought on household food security in South-western Uganda: Coping responses and determinants - Twongyirwe, Ronald; Mfitumukiza, David; Barasa, Bernard; Naggayi, Barbara R; Odongo, Hannington; Nyakato, Viola; Mutoni, Grace (Elsevier B.V, 2018)
Food insecurity is a region–wide problem in Sub-Saharan Africa, exacerbated by severe drought, with devastating impacts at the household level. However, farmers' coping strategies and their determinants remain under– documented. In this study, we: 1) characterise relationships between perceptions of drought and food insecurity and corresponding household coping responses, 2) compare livelihood characteristics of farmers that perceived food insecurity as a problem and those who did not, and 3) investigate how household-level characteristics correspond to household coping strategies. Our study is exploratory in nature: we administered a questionnaire to 140 farmers in Isingiro district in South-west (SW) Uganda whose livelihood is predominantly dependent on crop production. We employ binomial and multinomial logistic regression models to identify the determinants of the respondents’ perceptions, how household characteristics correspond to household perceptions of food insecurity, and factors that affect coping responses. Our data show that 68.6% of the respondents perceived food insecurity as a problem in their household. Access to credit for crop cultivation increased the likelihood (p < 0.05) that farmers will be more aware and concerned about household food security status. Farmers were more likely to use the credit as a buffer against food insecurity. Whilst drought is widely perceived (by 95.6%: 133) as a problem contributing to food insecurity, the coping responses are wide-ranging. However a considerable 13% (of the total) reported to be “doing nothing” to respond to the drought effects. Notably, farmers that did not perceive food insecurity as a problem have higher (p=0.01) off-farm incomes and larger (p=0.00) farm sizes on average compared to those that did. Significant (p < 0.05) determinants of coping strategies include a combination of size of farmland, total income from crops, number of livestock and marital status. Broadly, our study indicates that households believe they are most at–risk of drought–induced food insecurity. Access to credit and alternative means of livelihood may offer resilience building options.
Perceived effects of drought on household
Keywords: Food security, Drought ,Livelihood,s Coping responses, Determinants